Exploring the Expert Group Cooperative Learning Model for Arabic Qirā’ah Material Acquisition - Nuraeni, Maya; Al-Houdy, Mohammed Ismael (UIN Sunan Gunung Djati Bandung, 2024)
Students' ability to pronounce sentences and determine meaning is still an obstacle in learning to read linguistic and non-linguistic Arabic. This study aimed to determine how effectively students learn to read before and after using the